Respuesta :
Greetings!
Answer:
y = [tex]\frac{-2}{3}[/tex]x - 4
Step-by-step explanation:
Firstly, you must find the gradient. This is found using the following formula:
[tex]\frac{y2 - y1}{x2 - x1}[/tex]
Make sure that the x2 and y2 values are in the same coordinate set:
Let's set (-8 , 2) as y1 and x1, y1 = 2 and x1 = -8
That means that (1 , -4) is y2 and x2, y2 = -4 and x2 = 1
Plug the values in:
[tex]\frac{-4-2}{1 - - 8}[/tex]
Simplified:
[tex]\frac{-6}{9}[/tex]
Or -2/3
So the gradient is [tex]\frac{-2}{3}[/tex]
Now, using the following equation of a line formula:
y - y1 = m(x - x1)
Where m is the gradient and y1 and x1 are two coordinates, we can plug these values in:
y1 = 2
x1 = -8
m = -2/3
y - 2 = 2/3(x - - 8)
We need to get rid of the two third fraction so we multiply the whole equation by three to cancel it out:
y * 3 = 3y
-2 * 3 = -6
-2/3 * 3 = -2
3y - 6 = -2(x - - 8)
The negative and the subtract makes it a positive:
3y - 6 = -2(x + 8)
Now we can multiply the bracket out:
-2 * x = -2x
8 * -2 = -18
So:
3y - 6 = -2x - 18
The slope form is usually:
y = mx + c
So we need to move the -6 over to the other side making it a positive 6:
3y = -2x -18 + 6
3y = -2x -12
Divide all the equation by three to get 1y:
y = [tex]\frac{-2}{3}[/tex]x - 4
Which is the equation!
Hope this helps!
Answer: y=−2/3x−10/3
Step-by-step explanation: m=y2−y1 / x2-x1
x1=−8 , y1=2, x2=1, y2=−4.
m=(−4)−(2) / (1)−(−8)= −6/9= −2/3.
b=2 −(−2/3)x(−8)= −10/3 .
y= −2/3x−10/3.
Hope this helps
PLEASE MARK BRAINLIEST